2017
DOI: 10.1016/j.neo.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Everolimus with Sorafenib for Solid Renal Tumors in Tsc2+/− Mice Is Superior to Everolimus Alone

Abstract: Tuberous sclerosis (TSC) is an inherited tumor syndrome caused by mutations in TSC1 or TSC2 that lead to aberrant activation of mTOR and development of tumors in multiple organs including the kidneys. The mTOR inhibitors rapamycin and everolimus (rapalogs) have demonstrated clinical efficacy in treating TSC-associated tumors including renal angiomyolipomas. However, tumor responses are usually only partial, and regrowth occurs after drug withdrawal. TSC-associated tumors are highly vascular, and TSC patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…EVL has been shown to increase the activity of SFN by targeting different intracellular targets and can reverse resistance to SFN. Synergistic interactions between SFN and EVL have been shown in studies of several cancers such as renal, hepatic, and pancreatic cancers (4)(5)(6)(7)(9)(10)(11).…”
Section: : Tumor Growth Regression Was Observed Only In the Mice Treated With The Combination Of Sfn-evl Histological Analysis Revealed Nmentioning
confidence: 87%
See 1 more Smart Citation
“…EVL has been shown to increase the activity of SFN by targeting different intracellular targets and can reverse resistance to SFN. Synergistic interactions between SFN and EVL have been shown in studies of several cancers such as renal, hepatic, and pancreatic cancers (4)(5)(6)(7)(9)(10)(11).…”
Section: : Tumor Growth Regression Was Observed Only In the Mice Treated With The Combination Of Sfn-evl Histological Analysis Revealed Nmentioning
confidence: 87%
“…However, recurrent and progressive osteosarcoma is a recalcitrant disease. Sorafenib (SFN), an inhibitor of various tyrosine protein kinases (2,3), reduces tumor microvessel density and shows anti-proliferative activity in various solid tumors (4)(5)(6)(7).…”
Section: : Tumor Growth Regression Was Observed Only In the Mice Treated With The Combination Of Sfn-evl Histological Analysis Revealed Nmentioning
confidence: 99%
“…A recent clinical trial of cabozantinib has shown significantly improved overall and progression-free survival of patients with advanced renal cell carcinoma [33]. Expression of VEGFR1 is increased and Akt is activated in TSC-associated renal tumors [19], [34]. Further investigations may, therefore, be worthwhile to compare CB-839 combined with cabozantinib with rapamycin or its analogs for TSC-associated renal lesions in Tsc2 +/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Later, researchers found that mTOR1 plays a central role in the process of angiogenesis through multifactorial ways, including promoting VEGF-A expression by HIF-1α dependent and HIF-1α independent mechanism ( Dodd et al, 2015 ). Based on this hypothesis, additional experiments have suggested that a combination of rapalogs (Rapamycin and its analogs) and angiogenesis inhibitors, such as everolimus plus sorafenib, may significantly decrease the tumor size and improve the therapeutic efficacy by inhibiting mTORC1 and the mitogen-activated protein kinase (MAPK) pathway ( Yang et al, 2017 ), which is superior to the treatment with single rapalogs alone. Another study also found that angiogenesis inhibitors (sunitinib and bevacizumab) have therapeutic effects on TSC-related tumors, although they are not as effective as rapamycin ( Woodrum et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%